AN EXAMINATION OF EXTRINSIC MOTIVATION EFFECTS ON STUDENTS IN LEARNING ENGLISH IN HIGHER EDUCATION - Sopheng Tep (PROJECT (Professional Journal of English Education), 2022)
Researchers in developed countries have explored various types of motivation effects on students' English language learning, yet these are not broadly studied in developing country contexts, especially in higher education institutions. Hence, the objective of the current study is to examine four types of extrinsic motivation in order to evaluate which one is the most effective factor for motivating students to study English better than before. A quantitative method was employed, and data was collected through a survey questionnaire. 105 students were randomly selected from a university, which is one of the best private universities in Phnom Penh, Cambodia. The findings show that all four types of extrinsic motivation were crucial in being catalysts to push students to learn English better than before. The findings also revealed that external regulation (M = 4.89, SD = 0.17) was the most important factor among the other three types of extrinsic motivation. The results are vital for teachers of English and relevant stakeholders to motivate students to learn English. Finally, similar topics with a larger sample size should be conducted at other institutions across the country. Qualitative and mixed-method designs should also be considered. Keywords:  Cambodia, Motivation, Extrinsic Motivation, Four Types of Extrinsic Motivation